Whole genome-based reclassification of several species of the genus Nonomuraea. - Noureddine Bouras; Imen Nouioui; Guendouz Dif; Fawzia Chaabane Chaouch; Sherif S Ebada (PLoS ONE)
Earlier classification methods lacked the resolution necessary to delineate species comparing to current standards, particularly since a significant number of bacterial taxa were described before the integration of whole-genome sequencing into microbial taxonomy. With the advent of genome-based taxonomic approaches and integrated genomic metrics, including sequence similarity and phylogenomic frameworks, it has become essential to reevaluate the taxonomic status of older taxa defined before the era of genome-based microbial taxonomy. Applying these modern genomic criteria enables a more accurate assessment of species boundaries and helps to determine whether the old taxa represent distinct species or should be reclassified as synonyms, subspecies, or members of different genera. Such reclassification efforts are crucial for ensuring taxonomic accuracy, improving the reliability of comparative genomics, and maintaining stable and evolutionariy meaningful nomenclature. In this study, we re-evaluated the taxonomy of Nonomuraea using genome-based methods, including digital DNA-DNA hybridization (dDDH), average nucleotide identity (FastANI), average amino acid identity (AAI), and percentage of conserved proteins (POCP) analyses, complemented by phylogenomic analysis. Based on comprehensive genomic studies, our results support the elevation of both Nonomuraea roseoviolacea subsp. carminata and Nonomuraea roseoviolacea subsp. roseoviolacea to an unified species without subspecies distinction: Nonomuraea roseoviolacea (ATCC 27297T = BCRC 13406T = CBS 260.72T = CCM 3491T = CCRC 13406T = CGMCC 4.1072T = CIP 106924T = DSM 43144T = IFO 14098T = IMET 9751T = JCM 3145T = KCTC 9283T = NBRC 14098T = NCIB 11117T = NCIMB 11117T = NRRL B-16127T = VKM Ac-909T). Furthermore, we propose the reclassification of Nonomuraea recticatena, Nonomuraea roseola and Nonomuraea dietziae as subspecies within N. roseola. Consequently, we propose the establishment of the following two subspecies: Nonomuraea roseola subsp. roseola subsp. nov. (= ATCC 33579T = DSM 43767T = DSM 44323T = IFO 14685T = IMET 9576T = INA 1671T = JCM 3323 T = KCTC 9282T = NBRC 14685T = VKM Ac-1180T) and Nonomuraea roseola subsp. recticatena subsp. nov., comb. nov. (= DSM 43937T = IFO 14525T = INA 308T = JCM 6835T = KCTC 9279T = NBRC 14525T = VKM Ac-940T) and. In addition, we propose Nonomuraea harbinensis as later heterotypic synonyms of Nonomuraea ferruginea.